Strategies for improving measurement models for secondary data in public administration research: illustrations from the federal employee viewpoint survey - Somers, Mark John (2018)
This article builds on Fernandez et al.'s 2015 review of Federal Employee Viewpoint Survey (FEVS) research by focusing on two unexplored areas: measurement models and measurement quality. Employing the notion of an auxiliary measurement theory as an organizing framework, the author assesses the use of FEVS survey items to operationalize theoretical constructs and procedures in order to establish their psychometric quality. Results indicate that there is considerable variability in how FEVS items have been used to measure theoretical constructs, which is expressed as high levels of overlap across FEVS?derived scales. Inconsistency in the assessment of measurement quality is evident as well, with a bias toward convergent validity. Three cautionary tales are presented to demonstrate the fragility of FEVS data when used with a compromised auxiliary measurement theory. The article concludes with recommendations for future FEVS studies. - Reproduced.
Keywords: Federal Employee Viewpoint Survey (FEVS); Public administration - Research